Mitochondrial Dysfunction Is Involved in the Toxic Activity of Boric Acid against Saprolegnia - Ali, Shimaa E.; Thoen, Even; Evensen, Øystein; Wiik-Nielsen, Jannicke; Gamil, Amr A. A.; Skaar, Ida (PLOS ONE, 2014)
There has been a significant increase in the incidence of Saprolegnia infections over the past decades, especially after the banning of malachite green. Very often these infections are associated with high economic losses in salmonid farms and hatcheries. The use of boric acid to control the disease has been investigated recently both under in vitro and in vivo conditions, however its possible mode of action against fish pathogenic Saprolegnia is not known. In this study, we have explored the transformation in Saprolegnia spores/hyphae after exposure to boric acid (1 g/L) over a period 4–24 h post treatment. Using transmission electron microscopy (TEM), early changes in Saprolegnia spores were detected. Mitochondrial degeneration was the most obvious sign observed following 4 h treatment in about 20% of randomly selected spores. We also investigated the effect of the treatment on nuclear division, mitochondrial activity and function using confocal laser scanning microscopy (CLSM). Fluorescence microscopy was also used to test the effect of treatment on mitochondrial membrane potential and formation of reactive oxygen species. Additionally, the viability and proliferation of treated spores that correlated to mitochondrial enzymatic activity were tested using an MTS assay. All obtained data pointed towards changes in the mitochondrial structure, membrane potential and enzymatic activity following treatment. We have found that boric acid has no effect on the integrity of membranes of Saprolegnia spores at concentrations tested. It is therefore likely that mitochondrial dysfunction is involved in the toxic activity of boric acid against Saprolegnia spp.